Validation of the Ethiopian Version of eHealth Literacy Scale (ET-eHEALS) in a Population with Chronic Disease - Shiferaw KB (Dove Medical Press, 2020)
Kirubel Biruk Shiferaw Health Informatics Department, Debre Markos University, Debre Markos, EthiopiaCorrespondence: Kirubel Biruk Shiferaw Email birukkirubel@gmail.comBackground: Although the measurement scale developed by Norman and Skinner is the widely used scale to assess consumers’ eHealth literacy, translating and validating the scale for the language of the target population under consideration is necessary. Amharic is the official national language of Ethiopia, with 29.3% of native speakers.Methods: The total sample size calculated was 187 with 6% non-response rate. The internal consistency of the ET-eHEALS was measured using Cronbach’s alpha coefficient. Test–retest reliability was assessed by re-administering the ET-eHEALS questionnaire to 74 patients which is 40% of the total sample size. Construct validity was evaluated using exploratory factor analysis. The Kaiser–Meyer–Olkin (KMO) statistic and Bartlett’s test of sphericity were used to check the suitability of performing the factor analysis.Results: Of the respondents, 63.1% (n=118) were males and 55.1% (n=103) were aged between 18 and 35 years, with 57.2% (n=107) of the participants being educated to high school diploma level or higher. Cronbach’s alpha coefficient for the translated ET-eHEALS total score was 0.94. Test–retest reliability of ET-eHEALS total score was acceptable for both agreements and consistent with ICC (interclass correlation coefficient) of 0.92. The KMO ratio of sampling appropriateness was acceptable (0.91), and Bartlett’s test of sphericity was significant with p < 0.001. The EFA (exploratory factor analysis) extracted two factors based on an extraction principle of a minimum eigenvalue of one. The extracted factor explained 80.2% of the common variance which is 51.8% for factor 1 and 28.4% for factor 2. Except for item, item fit for both infit and outfit mean squares were within the adequate range (0.5– 1.5).Conclusion: This study depicted that ET-eHEALS is a consistent and valid instrument to evaluate Amharic-speaking chronic patients’ eHealth literacy level. Since there is no prior validation of eHEALS in low-income country, this finding may indicate important directions for further improvement in eHEALS item performance in resource-limited settings.Keywords: eHealth literacy, validation, developing country, chronic patients, eHEALS, ET-eHEALS